Increasing the Visual Effectiveness of Facebook Advertising and Its Position in the Online Advertising Market - Félegyházi, Zsolt (Acta Carolus Robertus, 2024)
The results show that Facebook still has an outstanding user base both globally and in Hungary. In terms of advertising, the platform can still achieve outstanding results, but it requires a well-considered, detailed strategy and a good understanding of the possible settings as well as of the target audience. The success of advertising depends on a number of factors, which advertisers need to consider and define individually. There is no doubt that one of the most important elements in advertising is the content itself, which is used to get the message across to the target audience. During a 2-week A/B test on Facebook, different visual advertising content was compared. During the study, there was a strong emphasis on video ads over visual content, thus examining which points are better exploited by entrepreneurs to achieve greater success in their advertising. Research shows that video ads perform best in Facebook's system, and as a result, they are clicked on more cheaply. Overall, optimizing and refining the visual content of Facebook ads is very important for effective ad campaigns. With the right creative and visual elements, constant optimization and refinement can create significant growth opportunities for your business.
Keywords: facebook; online marketing; video ads